Interesting Case of Acute Lung Oedema Complication of Dengue Hemorrhagic Fever-Hypercoagulability: Interesting Case of Acute Lung Oedema Complication of Dengue Hemorrhagic Fever-Hypercoagulability - Abshori, Nuril Farid; Kakay, Ferdinandus Stevanus; Ahdi, Iwal Reza (Clinical and Research Journal in Internal Medicine, 2025)
A B S T R A C T Background: Diagnosis and management of dengue hemorrhagic fever (DHF) can be challenging with confounding complications. Important confounding factors are conditions that alter hematologic parameters and prognosis of infection. We report a case of a patient with a positive DHF IgG result and hypercoagulation leading to Acute Lung Oedema (ALO), a serious condition with risk of respiratory failure leading to death. This is the first case to highlight the unique set of diagnostic and therapeutic challenges of DHF in this context. Case Presentation: A twenty-seven-year-old man presented with suspected DHF with thrombocytopenia and hypoalbumin. Pharmacologic and fluid therapy were optimal. However, the patient suddenly developed dyspnea leading to respiratory failure and had to be admitted to the intensive care unit. The patient also had severe infection as evidenced by D-dimer > 5,000 ng/ml and pulmonary edema, one of which was due to pulmonary embolism. This requires appropriate and rapid treatment, considering the patient is in critical condition. Conclusion: This patient faced two diagnostic challenges: the diagnosis of dengue fever with positive DHF IgG but with different clinical manifestations and the diagnosis of hypercoagulation related to pulmonary embolism. There were two therapeutic difficulties: that of balancing the risks and benefits of administering anticoagulants and steroids in a pulmonary embolism patient with DHF. As decisions in such cases are patient-specific, sharing individual experiences will help guide future therapeutic management decisions. Keywords: Acute Lung Oedema (ALO), Dengue Hemorrhagic Fever (DHF), Hypercoagulation